Penggunaan Bahasa Sarkasme dalam Media Sosial Instagram - M. Syaiful; Thasya Dinda; Tria Anggraini; Annisa Raihanun; Ayesha Rahmania; Eni Nurhayati (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This research aims to describe the form and meaning of netizens' use of sarcasm among netizens who are wiser in speaking on Instagram social media. This research is a descriptive qualitative type of research and the theory used in this research is sociolinguistic theory. The data collected by this research used note-taking, listening techniques and used a methodological approach. The results of this research are the use of sarcasm by netizens on the social media Instagram. Various forms of sarcasm were also found. These include forms of approval, rejection, forms of prohibition, conveying gossip, affirmations, orders, questions, statements and statements of greeting. Regarding the types of sarcasm language, it comes from changes in meanings that occur, including: 1) coarsening of meaning, 2) narrowing of meaning, 3) expansion of meaning.